(untitled) (Medico Legal Update, 2020)
Coronavirus disease 2019 (COVID-19) is a life-threatening global health scenario. The WHO (World Health Organization) has announced this disease as global issue. The severity of this disease causes highest death rates from December 2019-October 2020 world wide. There is an urgent need to develop medicines and vaccine to prevent the immune system of human. Medicinal plants and plant based drugs play a major role in preventing by provoking the immune system. This review discusses about the major global issue pandemic coronavirus disease (Covid -19) and the traditional medicines as preventive and curative agent in treating this global health issue.